From iceberg of pre-diabetes to poor glycemic control in diabetics: An elderly based study in Shiraz, South of Iran - Behnam Honarvar; Morteza Banakar; Nazi Hassani; Yasaman Movahednezhad; Zahra Gheibi; Kamran Bagheri Lankarani (International Journal of Preventive Medicine, 2019)
Background: Delay in diagnosis of diabetes mellitus (DM) in older adults is more catastrophic than other age groups. This study investigated the prevalence of pre-diabetes, DM, and glycemic control in the elderly. Methods: In this cross-sectional study, a sample of 412 older adults >60 years from Shiraz, Iran, were recruited through a multistage cluster random sampling. Demographic, clinical, and laboratory information were collected by interview, physical examination, and reviewing the medical records. Data were analyzed using SPSS 20. Results: Mean age was 68.1 ± 6.2 years and female-to-male ratio was 1.1. Out of all, 137 (33.2%) were diagnosed as diabetic including 128 (31%) as known cases and 9 (2.2%) as new cases of DM, whereas 275 (66.7%) were diagnosed as new cases of pre-diabetes. Multivariable analysis showed that low level of education (OR = 5.2, 95% CI: 1.5–16.6), hyperlipidemia (OR = 3.5, 95% CI: 2.1–5.8), liver disease (OR = 3.1, 95% CI: 1.4–6.9), and hypertension (HTN) (OR = 1.9, 95% CI: 1.1-3.2) were the most common predictors of DM in the elderly, respectively. Out of all diabetics, 33.6% had FBS >130 mg/dL and 25.5% had HbA1c >8%, whereas these figures were ≥100 mg/dL and ≥5.7% in 36.7% and 21.4% of pre-diabetics, respectively. Conclusions: The pre-diabetic elderly were mostly undiagnosed, while one-third to one-fourth of DMs had poor glycemic indices. These figures show the need for pre-diabetes and diabetes screening in the elderly, especially in those with low level of education, hyperlipidemia, liver disease, or HTN. Furthermore, regular monitoring of glycemic indices in the diabetic and pre-diabetic elderly is recommended.